Chinese external migration basic direction of the external economic strategy - Arzykulov A., А. А. (Journal of Oriental Studies, 2024)
Migration as the sign of process of globalization became the noticeablephenomenon of the XX century, and started influencing political, socialand economic and demographic position of the country. Considerablestructural changes in economy of China generated the biggest migratory wave in the world.